Space - "Snedden, Robert" (Belitha Press: Hong Kong, 1995)
Traces the story of how scientists have worked over many centuries to increase our understanding of space, and also shows that much is still to be discovered. Suggested level: intermediate, secondary
Keywords: Science-Outer space